KONSTRUKTIVISME FILSAFAT DALAM KONTEKS PENGEMBANGAN KETERAMPILAN BERBICARA DALAM PEMBELAJARAN BAHASA INGGRIS - Ramazan; Muhammad Hanif; Mochamad Nursalim; Agus Qowiyuddin (Center of Education Journal (CEJou), 2023)
Speaking skills are considered a very vital aspect of improving communication skills, self-confidence and career opportunities. In the context of English language teaching, learning speaking skills should be done effectively, focusing on hands-on experience and social interaction. The concept of philosophical constructivism provides the theoretical foundation for this study, with six key principles, including an emphasis on the active construction of knowledge by learners and the role of the teacher as a facilitator. The implications of constructivism in language learning include learner-centered learning, the teacher's role as a facilitator, active learning, the use of direct experience, social interaction, and reflection. The previous review highlights the application of constructivism in English language learning, with research covering the development of constructivist models, the enhancement of student understanding, and the application of constructivism learning theory in foreign language learning. Overall, the research confirms the importance of speaking skills in the context of English language learning and identifies constructivism as an effective approach. The implications and findings of the previous study provide deep and diverse insights into the application of constructivism in English language learning